Evolución biológica y cambio lingüístico - Contreras Domingo, Eugenio (Estudios Ingleses de la Universidad Complutense, 2005)
The present article reviews the contents of the book Explaining Language Change: An Evolutionary Approach, which explores language change from an abstract, biology-based evolutionary model from a Darwinian perspective. Owing to the fact that biology has for long been an inspiring source for research in language change, a brief comment on the relations between both fields of study (§1) seems to be in order. The theoretical basis for an evolutionary approach in the area of linguistics is presented in §2, followed by the exposition of the main aspects of the biological model on which the theoretical framework of the book is based (§3). The key characteristics of the model are included in sections §4 to §6. In §7 a comparison between this model and other theories of language change is made and the final section (§8) includes a brief conclusion.